Optimalisasi Potensi Desa Untuk Pencapaian Sustainable Development Goals - Salmun K. Nasib; Syahrizal Koem; Rakhmat Jaya Lahay (Jurnal Pengabdian Pada Masyarakat, 2022)
OPTIMIZATION OF VILLAGE POTENTIALS FOR THE ACHIEVEMENT OF SUSTAINABLE DEVELOPMENT GOALS. The community service program through disaster mitigation and community adaptation to utilize land was carried out in Bulontala Timur village. The purpose of this program is to increase the adaptive capacity of the community to support development in the village. The program uses several methods, namely; interviews, field observations, document studies, discussions. The main activities implemented in this program are disaster mitigation and food security programs. Disaster mitigation activities are packaged in the form of socialization and field action. The food security program is implemented in several activities, namely; socialization, community action to plant and providing agricultural equipment. The results achieved in the disaster mitigation program are the availability of early warning signs and evacuation routes as well as the distribution of tree planting locations. The result of food security activities is the availability of yards of people's homes that have been planted with seeds and seeds of spice plants. These two main programs are to support the achievement of indicators on the Village Building Index and Village SDGs in East Bulontala village.